2018
DOI: 10.1038/s41564-018-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of aminoglycoside antibiotics enhances host resistance to viral infections in a microbiota-independent manner

Abstract: Antibiotics are widely used to treat infections in humans. However, the impact of antibiotic use on host cells is understudied. Here we identify an antiviral effect of commonly used aminoglycoside antibiotics. We show that topical mucosal application of aminoglycosides prophylactically increased host resistance to a broad range of viral infections including herpes simplex viruses, influenza A virus and Zika virus. Aminoglycoside treatment also reduced viral replication in primary human cells. This antiviral ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 55 publications
8
85
1
Order By: Relevance
“…There has been a growing body of evidence that antibiotics can have a wide range of effects on the host (26). One study of particular note determined that aminoglycoside antibiotics are capable of altering the innate immune response in mice, which resulted in antiviral activity against both DNA and RNA viruses (19). They also found that these antibiotics function in a microbiota-independent manner (19), similar to our observations.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…There has been a growing body of evidence that antibiotics can have a wide range of effects on the host (26). One study of particular note determined that aminoglycoside antibiotics are capable of altering the innate immune response in mice, which resulted in antiviral activity against both DNA and RNA viruses (19). They also found that these antibiotics function in a microbiota-independent manner (19), similar to our observations.…”
Section: Discussionsupporting
confidence: 85%
“…Our group and others have used antibiotics to deplete the host microbiota to study virus-host-microbiota interactions (6,(11)(12)(13)(14). However, antibiotics can have microbiota-independent effects, and alter host metabolic pathways, gene expression profiles, and immune cell function (15)(16)(17)(18)(19). Specifically, antibiotics can alter the host interferon response (19), alter immune cell homing to intestinal tissues (20,21), and can have noncanonical effects on viruses, such as altering plaque size or exacerbating certain viral infections (15,22).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is relatively difficult to achieve micromolar EC50 in vivo. For example, aminoglycoside antibiotics, kasugamycin and neomycin were successfully tested against ZIKV, FLUAV, and HSV-2 infections in mice (Gopinath et al, 2018). Polyether antibiotic salinomycin also showed anti-FLUAV effect in mice (Jang et al, 2018).…”
Section: Evaluation Of Bsaas In Animal Modelsmentioning
confidence: 99%